Price discovery and arbitrage linkage in the Indian agricultural commodity futures market: a study of gram futures - Pushpa L Trivedi; Vishal V Nair (Agricultural Economics Research Review, 2023)
This study has attempted to empirically examine the price discovery function of futures market and arbitrage linkage between spot and futures markets for gram. The main findings are that (i) the futures market plays a leading role in price discovery but the spot market cannot be considered as a pure satellite, (ii) there is an impact of seasonality as the futures and spot prices are not co-integrated for the lean season contract, and (iii) the arbitrage linkage between spot and futures markets is weak.